Newspapers’ dependency from press agencies in Spain (Communication & Society, 2009)
The dialectics between printed press and news agencies have become an interesting field of study not only for academics, but also for media practitioners. Though some of them flatly speak about newspapers being dependent from news agency reports, the truth is that little progress has been made in researching this phenomenon and the circumstances surrounding it. This article tries to shed some light on this issue, by focusing on the empirical research of newspapers and news agencies reports and studying the factors that shape this interaction.